(untitled) (Journal of Rashid Latif Medical College, 2024)
Objective: The aim of this study is to present a thorough overview of asthma during pregnancy and to summarize the state of the art and to advance patients' and doctors' understanding of the significance of appropriate asthma care during pregnancy. Methods: A comprehensive literature search in PubMed, Medline, and Taylor and Francis was conducted. We have searched for review articles as well as prospective and retrospective studies published in English, investigating the bilateral relationship between asthma and pregnancy, using the key words mentioned below. Manual search through both national and international guidelines as well as relevant journals and publications on the topic was also conducted. Results: Several studies have highlighted the significant impact of asthma on pregnancy outcomes. Maternal asthma is associated with increased risks of low birth weight, preterm delivery, and preeclampsia. Pregnancy complications linked to asthma include gestational diabetes and placental abnormalities. Asthma exacerbations during pregnancy are linked to a higher incidence of cesarean sections. Conclusions: To reduce the negative effects on the mother and the fetus/neonate, it is crucial to have optimal asthma management and to avoid, diagnose, and treat exacerbations. Active asthma care is advised during pregnancy, according to guidelines. Keywords: Asthma, Pregnancy, Neonatal, COVID-19